2009
DOI: 10.1002/macp.200800484
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Large‐Area, Transferable Colloidal Monolayers Utilizing Self‐Assembly at the Air/Water Interface

Abstract: A versatile and simple method is presented for the rapid fabrication of close‐packed colloidal 2D crystals with large domain sizes by floating and redeposition of colloidal monolayers at the air/water interface. A detailed analysis of the particle surface transformation and packing during the individual steps of the monolayer fabrication process has been conducted. It was found that the quality of the monolayer depends on parameters like colloidal particle distribution on the initial substrate, subphase pH, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
172
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(173 citation statements)
references
References 38 publications
1
172
0
Order By: Relevance
“…111,112 They can also be pre-assembled at a liquid interface and subsequently transferred to a solid substrate. [113][114][115][116] The choice of assembly technique depends on the requirements with respect to the area to be coated, which have recently been discussed in detail. 52,117 Colloidal monolayers can be especially valuable as templates or masks for etching or evaporation processes to create functional surface nanostructures or coatings.…”
Section: (D) Multiple Porositiesmentioning
confidence: 99%
“…111,112 They can also be pre-assembled at a liquid interface and subsequently transferred to a solid substrate. [113][114][115][116] The choice of assembly technique depends on the requirements with respect to the area to be coated, which have recently been discussed in detail. 52,117 Colloidal monolayers can be especially valuable as templates or masks for etching or evaporation processes to create functional surface nanostructures or coatings.…”
Section: (D) Multiple Porositiesmentioning
confidence: 99%
“…The increased electrostatic repulsion counteracts the attractive van der Waals and capillary forces. Consequently, the particles remained more mobile at the interface, resulting in more ordered monolayers [20,22,23]. Thus, at pH 3, particles that approach each other closely (i.e.…”
Section: Surface Structure Fabrication and Characterizationmentioning
confidence: 99%
“…For example, Pan et al [21] introduced a dynamic interface, by stirring the aqueous subphase, to facilitate colloidal crystal formation at the air/water interface. Retsch et al [22] reported a two-step procedure in which colloids are applied to a glass slide by spin-coating. Subsequently, a colloidal monolayer was formed upon immersion of the glass slide in an aqueous surfactant solution [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As recently reviewed in detail by Jonas et al [6], MCC templates can be achieved by a variety of methods, including dip-coating, spin-coating, slope self-assembly, etc. [7][8][9][10][11][12]. Regarding infiltration and replication strategies, evaporation deposition, electrochemical deposition, and solution/sol-based infiltration methods are mainly included [13][14][15].…”
Section: Introductionmentioning
confidence: 99%